Advanced Composites and Applications: Book of Abstracts :﻿ February 13th, 2024 - 82nd International Scientific Conference of the University of Latvia (University of Latvia, 2024)
Traditionally, the session ‘Advanced Composites and Applications’ was organized by the Institute for Mechanics of Materials of the University of Latvia (LU MMI) on 13.02.2024 as a part of the annual 82nd scientific conference of the University of Latvia. The official language of the section is English. The duration of the presentation was 10 minutes. The section was devoted to the discussion of the recent results within the following topics: -structure and properties of polymers and polymer-based composites; -long-term properties, creep, and environmental ageing; -composites for advanced applications; -mechanical aspects of technology; -multifunctional properties.
Keywords: structure and properties of polymers and polymer-based composites; composites for advanced applications; long-term properties; creep; environmental ageing; Research Subject Categories::NATURAL SCIENCES::Chemistry; Research Subject Categories::NATURAL SCIENCES::Physics